2006
DOI: 10.1074/jbc.m513786200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ-mediated Regulation of Neural Stem Cell Proliferation and Differentiation

Abstract: Peroxisome proliferator-activated receptor ␥ (PPAR␥) plays an important role in insulin sensitivity, tissue homeostasis, and regulating cellular functions. We found high-level expression of PPAR␥ in embryo mouse brain and neural stem cells (NSCs), in contrast to extremely low levels in adult mouse brain. Here, we show that PPAR␥ mediates the proliferation and differentiation of murine NSCs via upregulation of the epidermal growth factor receptor and activation of the ERK pathway. Cell growth rates of NSCs prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 35 publications
6
133
1
Order By: Relevance
“…We used a lentiviral vector-mediated short hairpin RNA (LV-shRNA) system to effectively knockdown of PPARγ1 and PPARγ2 as previously described (9,14). Treatment with shRNA-P15, which effectively inhibits PPARγ expression, significantly increased number of the safranin-positive stained cells consistent with formation of mature CTMCs (Fig.…”
Section: Analysis Of Differentiation On Pparγ-knockdown Bmmcsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a lentiviral vector-mediated short hairpin RNA (LV-shRNA) system to effectively knockdown of PPARγ1 and PPARγ2 as previously described (9,14). Treatment with shRNA-P15, which effectively inhibits PPARγ expression, significantly increased number of the safranin-positive stained cells consistent with formation of mature CTMCs (Fig.…”
Section: Analysis Of Differentiation On Pparγ-knockdown Bmmcsmentioning
confidence: 99%
“…In this regard, we have recently reported that PPARγ expressed in neural stem cell dramatically suppresses their differentiation into maturate neurons (9). This suggests the possibility that bone-marrow progenitors might be targets of PPARγ-mediated regulation of differentiation into mature mast cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30) While PPARγ is expressed in the fetal brain as a factor involved in cellular development, its expression is quite limited in the healthy mature brain. 31) However, it has been suggested that while the PPARγ pathway is necessary for the growth of undifferentiated neural stem cells, it also plays an important role in maintaining the undifferentiated state. 32) Furthermore, a recent report on central PPARγ showed that cerebral ischemia increases the expression of PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, brain development abnormalities were reported in PPARg ¡/¡ and PPARg ¡/C mice embryos. 18 Various, and sometimes discordant, effects of PPARg agonists were also observed in a variety of neural cell models (reviewed in ref. 19).…”
Section: Role Of Pparg In Hcmv Neuropathymentioning
confidence: 99%